Papal policies on clerical sexual abuse: god weeps - Formicola, Jo Renée (Peter Lang, 2019)
God weeps -- The beginnings -- Pope John Paul II, the flummoxed -- Pope Benedict XVI, the rigid -- Pope Francis, the inconsistent -- God still weeps.